Folly Beach, South Carolina. Survey Report on Beach Erosion Control and Hurricane Protection. Appendixes. - CORPS OF ENGINEERS CHARLESTON SC CHARLESTON DISTRICT (1979)
Contents: The Study and Report, Resources and Economy of the Study Area, Problems and Needs, Material Investigations, Estimated Benefits, Design and Cost Estimates, Project Formulation, and the Selected Plan. Appendixes to final report, AD-A115 709. Original contains color plates: All DTIC and NTIS reproductions will be in black and white.